Brincadeiras de crianças diagnosticadas com transtorno do espectro autista na educação infantil: uma revisão bibliográfica - Duarte, Renata Silva Lima (2022)
This research contributes to a resizing of the role of games in the education of children with Autistic Spectrum Disorder (ASD), through a bibliographic review of three national journals from 2009 to 2019: Revista Educação Especial, Revista Brasileira de Educação Especial and Educação Especial em Debate. The search for articles was made with the following keywords combined with each other and separately: “children with ASD”, “plays”, “Early Childhood Education” and “autism”. Based on the selected articles, we aim to obtain answers to these questions: how are characterized the children diagnosed with ASD? How are games, their possibilities and limits related to them in publications? How are the games of children with ASD, especially make-believe, presented in the journals selected for this investigation? Such questions were answered by reading the articles found and according to the concepts related to human development, “defectology” and games in the historical-cultural perspective approached by Vigotski. According to the analyses, we concluded that games and educational interventions performed by adults during the games enhance the development of children in make-believe, by helping them to learn about their own life contexts, in which they share social meanings and collaborate to build senses aimed at playing and the experienced social relationships. The articles also showed that games and games are present in Early Childhood Education because they are activities that allow learning and development of children.